In factorization by regrouping, we should remember that any regrouping of the terms in the given expression may not lead to factorization. We must observe the expression and come out with the desired regrouping by trial and error.

1) Rearranging the expression so as to form groups.

2) Find the common factors from each group.

1) 2xy + 3 + 2y + 3x

2xy + 3 + 2y + 3x

Rearranging the expression, as 2xy + 2y + 3x + 3

=

Common factor from 1st group = 2y

Common factor from 2nd group = 3

= 2y ( x + 1) + 3( x + 1)

Now there are two terms, take common binomial factor (x + 1)

= (x + 1) (2y + 3)

________________________________________________________________

2) Factorize 6xy – 4y + 6 – 9x.

6xy – 4y + 6 – 9x

Rearranging the expression, as 6xy - 9x - 4y + 6

=

Common factor from 1st group = 3x

Common factor from 2nd group = - 2

= 3x( 2y - 3) - 2( 2y - 3)

Now there are two terms, take common binomial factor (2y - 3)

= (2y - 3) (3x - 2)

________________________________________________________________

3) Factorize : 15pq + 15 + 9q + 25p

15pq + 15 + 9q + 25p

=

= 3q (5p + 3) + 5 (3 + 5p)

= 3q ( 5p + 3) + 5(5p + 3) [ use commutative property for addition]

= (5p + 3)(3q + 5)

• Factorization by common factor

• Factorization by Grouping

• Factorization using Identities

• Factorization of Cubic Polynomial

• Solved Examples on Factorization